2017
DOI: 10.1111/cga.12252
|View full text |Cite
|
Sign up to set email alerts
|

D40/KNL1/CASC5 and autosomal recessive primary microcephaly

Abstract: Autosomal recessive primary microcephaly (MCPH) is a very rare neuro-developmental disease with brain size reduction. More than a dozen loci encoding proteins of diverse function have been shown to be responsible for MCPH1-13. Mutations in the D40/KNL1/CASC5 gene, which was initially characterized as a gene involved in chromosomal translocation in leukemia and as a member of the cancer/testis gene family, was later found to encode a kinetochore protein essential for mitotic cell division and to cause MCPH4. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In current reports, researchers have summarized the biofunctions of CTAs into three aspects: transcriptional regulation, mitotic fidelity, and protein degradation [6]. ZNF165 (C2H2 zinc finger transcription factor, also known as CT53) regulates the expression of genes in TGFβ pathway to promote tumorigenesis [38,39]; TEX14, CASC5, TTK, and NUF2 all participate in the kinetochore assembly process of tumor cells [40,41]; MAGE-A3/6 interacts with TRIM28 to regulate the proteasome-dependent degradation of tumor suppressors [30,42]. PRM1, however, acts as a DNA binding protein in spermatogenesis, and its aberrant location into somatic cell nucleus will lead to chromatin condensation and impair proliferation of Hela and E.coli [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In current reports, researchers have summarized the biofunctions of CTAs into three aspects: transcriptional regulation, mitotic fidelity, and protein degradation [6]. ZNF165 (C2H2 zinc finger transcription factor, also known as CT53) regulates the expression of genes in TGFβ pathway to promote tumorigenesis [38,39]; TEX14, CASC5, TTK, and NUF2 all participate in the kinetochore assembly process of tumor cells [40,41]; MAGE-A3/6 interacts with TRIM28 to regulate the proteasome-dependent degradation of tumor suppressors [30,42]. PRM1, however, acts as a DNA binding protein in spermatogenesis, and its aberrant location into somatic cell nucleus will lead to chromatin condensation and impair proliferation of Hela and E.coli [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…KNL1 is overexpressed in colorectal tumors, and the downregulation of KNL1 leads to cell apoptosis and inhibits the development of colorectal cancer cell lines [13]. KNL1 is widely expressed in primary tumors, such as lung cancer [30]. Here, we used data from TCGA to study the correlation between KNL1 and patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, the KMN network gene KNL1 has been described as an essential platform for checkpoint signals in kinetocytes [29]. KNL1 plays a vital role in the mitotic division in chromosome conversion, the connection of mitotic chromosomes and hammers, the interaction between signals and assembly checkpoint (SAC) settings, as well as several regulatory structures and proteins [30]. Previous studies have shown that KNL1 chromosomal interference accelerates the alignment of the mitotic division and failure of checkpoints, resulting in the absence of microtubular attachment and silk dots [13].…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved C-terminal of KNL1 forms the RWD domain that interacts with NSL1, a component of the MIS12 complex, to stabilize the KMN network (Petrovic et al, 2014). KNL1 is required for spindle assembly checkpoint formation, kinetochore assembly, and proper chromosomal segregation (Takimoto, 2017). This conserved scaffold protein aids in the attachment of condensed chromatin to the mitotic apparatus and is a signaling hub during early mitosis, playing an essential role in mitotic division (Ghongane et al, 2014).…”
Section: Introductionmentioning
confidence: 99%